2015
DOI: 10.3748/wjg.v21.i22.6872
|View full text |Cite
|
Sign up to set email alerts
|

Induction of endoplasmic reticulum-derived oxidative stress by an occult infection related S surface antigen variant

Abstract: AIM:To investigate the mechanism of endoplasmic reticulum (ER) stress induction by an occult infection related hepatitis B virus S surface antigen (HBsAg) variant. METHODS:We used an HBsAg variant with lower secretion capacity, which was a KD variant from a Korean subject who was occultly infected with the genotype C. We compared the expression profiles of ER stress-related proteins between HuH-7 cells transfected with HBsAg plasmids of a wild-type and a KD variant using Western blot. RESULTS:Confocal microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…ER stress caused the release of calcium from the ER to the cytoplasm, which induced intracellular reactive oxygen species (ROS). Interestingly, we also found that the expression of antioxidant proteins such as superoxide dismutase (MnSOD and CuZnSOD), HO-1, and catalase were substantially reduced in the KD variant [18]. These data strongly implied the pathway of ER stress-linked ROS generation [78].…”
Section: Mutations In the Hbsag Region Related To Er Stressmentioning
confidence: 90%
See 1 more Smart Citation
“…ER stress caused the release of calcium from the ER to the cytoplasm, which induced intracellular reactive oxygen species (ROS). Interestingly, we also found that the expression of antioxidant proteins such as superoxide dismutase (MnSOD and CuZnSOD), HO-1, and catalase were substantially reduced in the KD variant [18]. These data strongly implied the pathway of ER stress-linked ROS generation [78].…”
Section: Mutations In the Hbsag Region Related To Er Stressmentioning
confidence: 90%
“…In our previous study, we introduced a total of 10 types of HBsAg variants from a Korean occult cohort that could be divided into five groups according to intracellular and secretion levels of HBsAg and virions [77]. In our further study of these variants, we investigated an occult infection-related HBsAg variant (KD variant with five mutations: W36L, T47K, N52D, V184A, and F220L), which belonged to group II and showed a high level of intracellular HBsAg due to an almost negative secretion capacity [18].…”
Section: Mutations In the Hbsag Region Related To Er Stressmentioning
confidence: 99%
“…35 It has been reported that the HBsAg variant activates ER-related genes and induces ER stress that mediates the induction of reactive oxygen species, NO and apoptosis in similar manners. 36 In addition, the PERK pathway is involved in NO-induced apoptosis in endothelial cells under high-glucose conditions. 37 Moreover, NO-induced apoptosis in pancreatic β-cells is mediated by the ER stress pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, during chronic HBV infection, the integration of viral DNA into the host chromosome may cause viral genomic disruptions and then induce a dysregulation of surface protein production, which in turn leads to the overexpression of LHBs and the accumulation of MHBs and SHBs in the ER [ 6 , 11 ]. The aggregation of mutant HBV surface antigen variants were reported to cause ER stress [ 4 , 33 ]. Persistent ER stress activates autophagy, which is beneficial for hepatocyte survival and viral persistence.…”
Section: Discussionmentioning
confidence: 99%